PENDIDIKAN ISLAM SEBAGAI TRANSFORMASI SOSIO-KULTURAL: ANALISIS TEORI TARBIYAH, TA’LIM DAN TA’DIB DALAM KONTEKS KONTEMPORER - Mahmud; Mohamad Erihadiana; Dayat Indra Hidayat; Rizki Imanudin; Aris Rahman (LP2M IAIN Sultan Amai Gorontalo, 2026)
Islamic education plays a crucial role not only in shaping the holistic development of human beings but also as a driving force for social and cultural transformation. This study is motivated by global changes, moral crises, and modernization challenges that require Islamic education to adopt a relevant and contextual approach. The purpose of this research is to examine how the concepts of tarbiyah, ta’lim, and ta’dib can be integrated to form an Islamic educational model oriented toward socio-cultural transformation. The study employs a Systematic Literature Review (SLR) approach based on the PRISMA framework, reviewing 158 scholarly articles and selecting 9 that meet the inclusion criteria. The findings reveal that the integration of these three concepts establishes a holistic Islamic education model that balances spiritual, intellectual, and social dimensions. Islamic education functions as a moral and cultural agent of change capable of responding to globalization and secularization. This research contributes conceptually to developing a modern Islamic education curriculum grounded in the values of tawhid, morality, and social ethics.